Enhancing Anaerobic Endurance in Student Futsal Players through Small-Sided Games Combined with High-Intensity Interval Training - M. Fu'ad Fahrudin; Gigih Siantoro; I Dewa Made Aryananda Wijaya Kusuma; Imam Syafii; David Agus Prianto; Bayu Agung Pramono; Muhammad Kharis Fajar (OVS LLC, 2024)
Objectives. Futsal is a team sport that requires anaerobic support tactics and playing techniques, some of which include attack versus defend and high-intensity interval training (HIIT).  The aim of this study was to determine the effect of training small-sided games with high-intensity interval training on the anaerobic endurance of futsal players. Materials and methods. In this study, a one-group pretest-posttest design was used. The study population consisted of 25 players. 16 players were selected with an average age of 15.9 ± 0.5 years, a height of 158.1 ± 5.79 cm, a body mass of 58.9 ± 9.79 kg, and an IMT of 19.9 ± 2.41. The research data were analyzed using the paired sample t-test. Results. Based on the results of the paired sample t-test, it was found that the sig (2-tailed) values were 0.002 < 0.005, indicating a significant increase in anaerobic endurance. Conclusions. It can be concluded that small-sided game training with high-intensity interval training contributes significantly to the improvement of anaerobic endurance in student futsal players.